WHITE SPACE DALAM IKLAN DI MEDIA CETAK - D. Hagijanto, Andrian (Nirmana, 1999)
Readers are often unware of advertisments published in print media%2C therefore the elements of communication design composed in the promotion process fail to reach the objectives. One of the methods use to gain attention from the readers so they focus their vision to the advertisment is by presenting the lay out using white space. This article is to discuss about white space in media advertisments%2C especially newspaper and magazines. Abstract in Bahasa Indonesia : Iklan pada media cetak terkadang dilewati begitu saja oleh pembaca%2C sehingga proses promosi yang dikemas dengan elemen desain komunikasi visual itu gagal mencapai tujuannya. Salah satu cara untuk menarik perhatian pembaca agar menghentikan sejenak kedua matanya dan mengamati iklan adalah dengan menciptakan layout iklan lewat peranan white space. Tulisan ini akan membahas mengenai white space di dalam iklan media cetak%2C khususnya koran dan majalah.